Banana Fiber Composite (SBP) - Epoxy As A Sound Absorbent Material - Khusnul Khotimah; Susilawati Susilawati; Harry Soeprianto (Natural B, Journal of Health and Environmental Sciences, 2014)
This research conducted to find the physical properties of the absorption of sound from banana stem fiber (Serat Batang Pisang / SBP) with epoxy matrix. The sound absorbent material made with a variety of different volume fraction composition. The comparison between the SBP and the volume fraction of the matrix is made of 30%: 70%, 40%: 60% and 50%: 50%. The method of research was done in three stages: making banana stem fiber, manufacturing composite and testing of composite SBP. Composite testing include physical properties (sound absorption). Preparation of the samples started by taking a banana stem, decomposition banana stem fiber, alkali treatment with NaOH 4%, then mixing the SBP with the epoxy matrix. Manufactured the composites by press the materials on the molding for 12 hours, then tested to find physical properties. Sound absorption test performed using a signal generator and a sound level meter with the principle of the impedance tube method through acoustic box approach as a reference. The results of the study showed that SBP with epoxy composites absorb up to 30% noise at 30% fiber volume fraction. Thus, SBP composites can absorb sound for low (f= 400 Hz) and medium frequency (f = 1000 Hz), based on the standard ISO 11654:1997 (E) where the minimum of sound absorption coefficient of acoustic materials is α = 0.15.